Optimal design of energy storage for load frequency control in micro hydro power plant using Bat Algorithm - Muhammad Ruswandi Djalal; Nasrun Kadir (Universitas Mercu Buana, 2022)
The rotational speed of a generator affects the frequency and voltage produced, where this change will affect the load side. For that we need a control equipment that can optimize the performance of micro-hydro. Therefore, we need a technology to optimize the performance of micro hydro by applying Load Frequency Control (LFC). LFC designed by implementing Superconducting Magnetic Energy Storage (SMES) and Capacitive Energy Storage (CES), this application will provide power compensation to reduce or even eliminate frequency oscillations caused by changes in consumer electrical power loads. To get optimal microhydro performance, it is necessary to set the right parameters for SMES and CES. SMES and CES parameter tuning in this study is proposed using the Bat Algorithm. The objective function used by this algorithm is to optimize the Integral Time Absolute Error (ITAE). For performance analysis, the system is tested with load changes, then the governor, turbine, and system frequency responses are analyzed. To test the reliability of the system, this study used several scenarios of a combination of control, SMES, CES, with conventional control based on Proportional, Integral, Derivative (PID). The right control parameters will improve system performance more optimally. Optimal system performance can be seen from the response of the governor, turbine, and minimum overshoot of the frequency, as well as the fast settling time for the system to switch to steady state conditions.